"e^x +x = 4"
Now we write this in a Lamber form i.e.
"1 = (4-x) . e^{-x}"
Rewrite this introducing u i.e.
let "u = 4 - x" such that;
"x = -u +4"
Replacing this back into the Lambert form, we have;
"1 = (4 - (-u+4)) . e^{-(-u+4)}"
"1= (\\cancel{4} + u - \\cancel{4}) .e^{u-4}"
"1 = u.e^{u-4}" Rewrite this again in lambert form;
"u.e^u = e^4" Solving this, we have;
"u.e^u = e^4 \u21d2 u = W_n (e^4)"
Where W is the Lambert function called the Omega constant
Now substituting this back to "u = - x +4" and solving for "x" ;
"\u21d2 -x +4 = W_n (e^4)"
"\\therefore x = - W_n (e^4) +4," "n\\isin \\Z"
Comments
Leave a comment